Pharmacokinetics of a Slower Clearing Tissue Plasminogen Activator Variant, TNK-tPA, in Patients with Acute Myocardial Infarction - Modi, Nishit B.; Eppler, Stephen; Breed, Judy; Cannon, Christopher P.; Braunwald, Eugene; Love, Ted W. (Thrombosis and Haemostasis, 1998)
The rapid clearance of t-PA from plasma requires administration by intravenous (IV) infusion. A slower clearing, fibrin-specific rt-PA variant may allow single intravenous bolus administration, thereby simplifying dosing. This study was designed to characterize the pharmacokinetics of the slower clearing, fibrin-specific tissue-plasminogen activator variant, TNK-tPA, in patients with acute myocardial infarction (AMI) following a single IV bolus injection. Single IV bolus doses of 5 to 50 mg of TNK-tPA were studied in an open-label, multicenter, dose escalation study. A total of 113 AMI patients were enrolled. Blood sampling for pharmacokinetics was conducted in eighty-two patients (72 men, 10 women), with 5 to 27 patients per dose. TNK-tPA was administered as an IV bolus over 5–10 s. Following IV bolus administration, there was a biphasic elimination of TNK-tPA from plasma. The initial phase had a mean half-life that ranged from 11 ± 5 to 20 ± 6 min and was followed by a terminal phase with a mean half-life that ranged from 41 ± 16 to 138 ± 84 min. Mean TNK-tPA plasma clearance was 125 ± 25 - 216 ± 98 ml/min, and the initial volume of distribution was 4.3 ± 2 - 8.4 ± 6 l. A decrease in TNK-tPA plasma clearance with increasing TNK-tPA dose was noted. In addition, women and patients with lower body weight or older age had a slower plasma clearance. In conclusion, TNK-tPA has a slower plasma clearance in patients with AMI than that reported for rt-PA, allowing administration as a single IV bolus.